(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2022)
The objective of this musical research article is to determine the behavior of pitches in the first piece of the Octoechos series by Colombian composer Hector González from the perspective of the theory of pitch class sets. They are derived as specific objectives: to determine and implement the pertinent analytical units, to analyze the melodic structure and codify it in the context of the pitch class sets (PCS) theory and finally to reveal the structural functionalities found in the piece. An analytical protocol consisting of the following parameters was applied: type of textures, PCS, normal form, prime form, interval vector, composer annotations. As a result, the PCS development map used in the piece and its structural implications in relation to the other parameters studied were obtained.